2014
DOI: 10.1002/tox.21945
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity of single‐wall carbon nanotubes to freshwater snail Lymnaea luteola L.: Impacts on oxidative stress and genotoxicity

Abstract: Mammalian studies have raised concerns about the toxicity of carbon nanotubes, but there is very limited data on ecogenotoxicity to aquatic organisms. The aim of this study was to determine eco-geno toxic effects of single walled carbon nanotubes (SWCNTs) in fresh water snail, Lymnea luteola (L. luteola). A static test system was used to expose L. luteola to a freshwater control, 0.05, 0.15, 0.30, 0.46 mg/L SWCNTs for up to 4 days. SWCNTs changed a significant reduction in glutathione, glutathione-S-transferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The newly hatched larvae (approximately 5000) were exposed to O-SWCNTs (50 mg L −1 ) for 72 h. During the exposure, approximately 300 larvae per time point (1,3,5,7,9,12,15,18,24,30,36,48, 60 and 72 h) were randomly sampled and thoroughly washed with distilled water. The larvae were homogenized and pipetted into a square quartz groove (side length: 5 mm; height: 1 mm), and then dried in a vacuum at 80°C.…”
Section: Uptake Kineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The newly hatched larvae (approximately 5000) were exposed to O-SWCNTs (50 mg L −1 ) for 72 h. During the exposure, approximately 300 larvae per time point (1,3,5,7,9,12,15,18,24,30,36,48, 60 and 72 h) were randomly sampled and thoroughly washed with distilled water. The larvae were homogenized and pipetted into a square quartz groove (side length: 5 mm; height: 1 mm), and then dried in a vacuum at 80°C.…”
Section: Uptake Kineticsmentioning
confidence: 99%
“…The toxicity, bioaccumulation and fate of SWCNTs in some freshwater organisms have been studied, such as Pseudokirchneriella subcapitata, 7 Daphnia magna, 8 Lymnea luteola 9 and Danio rerio. 10 Besides, the development toxicity of SWCNTs on rare minnow embryos and larvae was also investigated in our previous work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPO levels were significantly increased among controls and treatment groups in both tissues. Ali et al [30] have reported that oxidative stress is a major mechanism of ecotoxicity. GSH and LPO (Figure 3) were increased, and GST and catalase (Figure 4) were increased at lower concentrations and increased higher concentration, indicating that toxic effects were related to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The studies were done on several cell types from embryonic cells to adult cells such as haemocytes, gill cells, hepatopancreas cells and digestive gland cells. The majority of studies are on freshwater snails employing different species including Lymnaea stagnalis [158][159][160][161], Lymnaea luteola [162][163][164][165], Biomphalaria glabrata [166], Biomphalaria alexandrina [167,168], Marisa cornuarietis [169], Potamopyrgus antipodarum [170], Bellamya aeruginosa [171], Pila globose [172], Viviparous bengalensis [149] and Heleobia cf. australis [173].…”
Section: Gastropodsmentioning
confidence: 99%